Post-COVID-19 policy responses to climate change: beyond capitalism?. (2nd October 2021) - Dean, Mark; Rainnie, Al
ABSTRACT: Commentators across the political spectrum have interpreted the social, political and economic consequences of the COVID-19 pandemic and invariably suggested that, along with climate change, the COVID-19 pandemic requires an interventionist policy response from government. In this paper, we interpret definitions of green growth as 'mission-oriented approaches' to the 'twin crises' of the COVID-19 pandemic and climate change, examining the changing role of the state in confronting environmental issues in an era of climate and health pandemic. Both events have had, and will continue to have, important implications for work and employment. Thus, we evaluate the impact of COVID-19 on climate change, asking: to what extent have mission-oriented policy responses to COVID-19 impacted climate change action? We then broadly examine the impact of COVID-19 on labour globally and more closely, the possible impacts of a range of policy response options for Australia, assessing their position on a theoretical spectrum of 'ecological modernisation' that points to further policy development that can push responses beyond capitalism.